현사시나무 수피에서 분리한 Grandidentatin Isomer의 입체구조결정 - 권동주; Dong Joo Kwon; 김현석; Hyun Seok Kim; 이필호; Phil Ho Lee; 배영수; Young Soo Bae (목재공학, 2009)
The bark of Populus alba ${×}$ glandulosa was collected, air-dried and extracted with 70% aqueous acetone. Then it was successively partitioned with n-hexane, $CH_2Cl_2$, EtOAc and $H_2O$. Repeated Sephadex LH-20 column chromatography and preparative TLC on the EtOAc soluble fraction gave a grandidentatin isomer. The structure was elucidated as grandidentatin A (cis-2-hydroxycyclohexyl 6-O-p-coumaroyl-${β}$-D-glucopyranoside) on the basis of spectroscopic evidences such as $^1H$-NMR, $^{13}C$-NMR, 2D-NMR and MALDI TOF-MS spectrum followed by acid hydrolysis. Grandidentatin A was identified here for the first time in Populus alba ${×}$ glandulosa bark, and to the bset of our knowledge it has not been reported in any other literature. 현사시나무 수피를 채취하여 기건 시킨 후 70% 아세톤 용액으로 추출하고 농축한 후 헥산, 디클로로메탄, 에틸아세테이트 및 수용성으로 순차 추출하여 동결건조하였다. 에틸아세테이트 분획에 대하여 Sephadex LH-20 컬럼크로마토그래피와 분취 TLC를 반복적으로 수행하여 화합물을 분리하였다. 화합물의 구조는 산 가수분해와 $^1H$-NMR, $^{13}C$-NMR, 2D-NMR 및 MALDI TOF-MS 스펙트럼을 분석하여, grandidentatin A(cis-2-hydroxycyclohexyl 6-O-p-coumaroyl-${β}$-D-glucopyranoside)로 동정하였다. Grandidentatin A는 현사시나무 수피에서 처음 분리되었으며, 문헌에 보고되지 않은 신규화합물이다.